Saturn suprathermal O2+ and mass‐28+ molecular ions: Long‐term seasonal and solar variation. Issue 6 (28th June 2013) - Christon, S. P.; Hamilton, D. C.; DiFabio, R. D.; Mitchell, D. G.; Krimigis, S. M.; Jontof‐Hutter, D. S.
Abstract : [1] Suprathermal singly charged molecular ions, O2 + (at 32 Da/e) and the Mass‐28 ion group 28 M + (ions at 28 Da/e, with possible contributions from C2 H5 +, HCNH +, N2 +, and/or CO + ), are present throughout Saturn's 4–20 Rs (1 Saturn radius, Rs = 60, 268 km) near‐equatorial magnetosphere from mid‐2004 until mid‐2012. These 83–167 keV/e heavy ions measured by Cassini's CHarge‐Energy‐Mass Spectrometer have long‐term temporal profiles that differ from each other and differ relative to the dominant water group ions, W + (O +, OH +, H2 O +, and H3 O + ). O2 + /W +, initially 0.05, declined steadily until equinox in mid‐2009 by a factor of 6, and 28 M + /W +, initially 0.007, declined similarly until early‐2007 by a factor of 2. The O2 + /W + decline is consistent with Cassini's in situ ring‐ionosphere thermal ion measurements, and with proposed and modeled seasonal photolysis of Saturn's rings for thermal O2 and O2 + . The water ice‐dominated main rings and Enceladus plume depositions thereon are the two most likely O2 + sources. Enceladus' dynamic plumes, though, have no known long‐term dependence. After declining, O2 + /W + and 28 M + /W + levels remained low until late‐2011 when O2 + /W + increased, but 28 M + /W + did not. The O2 + /W + increase was steady and became statistically significant by mid‐2012, indicating a clear increase after a decline, that is, a possibly delayed O2 + "seasonal" recovery. Ring insolation is driven by solar UV flux which itself varies with the sun's 11 year activity cycle. The O2 + /W + and 28 M + /W + declines are consistent with seasonal ring insolation. No O2 + /W + response to the late‐2008 solar‐cycle UV minimum and recovery is evident. However, the O2 + /W + recovery from the postequinox baseline levels in late‐2011 coincided with a strong solar UV enhancement. We suggest a scenario/framework in which the O2 + observations can be understood. Key Points: Energized Saturn ring ionosphere O2+ ions show seasonal and solar variation. The long‐term O2+/W+ variation is not as anticipated after equinox. Energized local‐origin Mass‐28 ions initially show likely seasonal variation.